2022
DOI: 10.1002/ecs2.4003
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the efficacy of shell hash for the mitigation of intertidal sediment acidification

Abstract: Our objectives were twofold: (1) to determine whether the addition of shell hash to intertidal sediments would mitigate porewater acidification and (2) whether its effectiveness was dependent on the type of sediment as described by organic matter (OM) and particle grain size (PGS). Field experiments were conducted at two sites within Burrard Inlet, British Columbia; Maplewood Mudflats (MM), high in OM and silt and Whey-ah-Wichen/Cates Park (WAW), low in OM and an equal PGS among very coarse, coarse, fine sand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, the application of very finely crushed shell hash could have a negative effect by decreasing interstitial spaces in the sediment and thus, as seen with silt, decreasing sediment permeability. Recent studies investigating the efficacy of shell hash to mitigate acidification of intertidal sediments found it unsuccessful at raising pore-water pH of acidic sediments (Beal et al 2020, Doyle and Bendell 2022). Doyle et al (2022) found the addition of shell hash to be site dependent as it reduced variation in pH at an intertidal site with pH 8.03 but did not mitigate the pH of mud flats with pH 7.59.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the application of very finely crushed shell hash could have a negative effect by decreasing interstitial spaces in the sediment and thus, as seen with silt, decreasing sediment permeability. Recent studies investigating the efficacy of shell hash to mitigate acidification of intertidal sediments found it unsuccessful at raising pore-water pH of acidic sediments (Beal et al 2020, Doyle and Bendell 2022). Doyle et al (2022) found the addition of shell hash to be site dependent as it reduced variation in pH at an intertidal site with pH 8.03 but did not mitigate the pH of mud flats with pH 7.59.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigating the efficacy of shell hash to mitigate acidification of intertidal sediments found it unsuccessful at raising pore-water pH of acidic sediments (Beal et al 2020, Doyle andBendell 2022). Doyle et al (2022) found the addition of shell hash to be site dependent as it reduced variation in pH at an intertidal site with pH 8.03 but did not mitigate the pH of mud flats with pH 7.59. At this point it appears that more research is required to comprehensively understand the effects of shell hash on bivalve growth and survival.…”
Section: Abiotic Variation Among Beach Location and Effects On Clam G...mentioning
confidence: 99%
“…One of the beach locations in Okeover is a shell midden. Shell middens are prominent features along the coast of British Columbia and are being evaluated for their potential for mitigating the effects of OA in the region, as it is thought that dissolution of the shell hash will add TA back into the water and elevate pH (e.g., Doyle and Bendell, 2022;Kelly et al, 2011).…”
Section: Okeover Inletmentioning
confidence: 99%